Characteristics of Apis cerana (hymenoptera: apidae) and effects of diet variability on bee venom quality and quantity in Peninsular Malaysia - Abusabbah, Mohammed Omar A (2014)
The bee venom is a complicated chemical and pharmacological product, which has been used for healing several diseases for many centuries by different nations. The components of venom, especially melittin, phospholipase A2 and apamin are the main qualitative factors that affect its chemical properties. Few information on the effect of nutrition on the quality and quantity of the venom produced by bees are available, particularly of Apis cerana. In addition,providing information on the genetic basis of A. cerana in Peninsula Malaysia is highly required. Accordingly, this study aims to investigate the morphometric and phylogenetic of A. cerana, also to investigate the variation in the quality and quantity of the bee venom collected from different sites in Peninsula Malaysia, and the effect of the bee diet on the venom quality. Morphometric study of the A.cerana from different seven localities in Malaysia was performed and the morphometric variables were analysed by multivariate analyses. The analysis of variance (ANOVA) results showed that there were significant differences between means of the different locations, however, the principal component analysis and the discrimination analysis showed that the most important variable to discriminate between A. cerana were body weight and the stinger length. Based on the obtained results, there were no clear clusters observed indicating the high similarity between the A. cerana population in Malaysia. The Phylogenetic showed an acceptable divergence percentage of less than 1% between bee venom samples, implying that the DNA of A. cerana collected from different sites with different types of diets is completely typical, therefore the venom quality and quantity was found to be affected purely by the type of diet. Investigation the effect of the natural diet on the quality and quantity of bee venom revealed that the source of natural diets (pollen grains) was significantly affected the quality and quantity of bee venom. Bees that foraged on durian were the highest concentrations of the important components melittin, phospholipase A2 and apamin by 677.86±23.68, 477.95±7.75 and 136.10±3.98 μg/μl respectively, corresponding to the protein content, which was the highest among the seven plants (31.71%). Whereas, the quantity analysis resulted high weight of 7.65±0.25 μg was achieved by star fruit. The effect of carbohydrate and protein rich mixture was studied. The results showed that the venom produced by bees foraged on supplementedcarbohydrate diets, had melittin, phospholipase A2 and apamin of 535.21±17.73, 374.49±18.94 and 130.36±12.05 μg/μl respectively. The comparison of the alternative diets proved that the protein rich mixture is better than both sucrose diet and the natural diet for yielding venom with high quality. Relocation of the hives from their original locations to the area with different flora led to obvious changes in the quality and quantity of the bee venom. The results showed that the most significant difference was observed in the concentration of the phospholipase A2 between pink power (420.85±13.15μg/μl) and star fruit (360.41±15.74μg/μl).